PENGOLAHAN SAGU BERBASIS ZERO WASTE DI KABUPATEN MANOKWARI - Bertha Mangallo; Darma; Selmi Dedi (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
The Community Partnership Program aims to build partnerships with sago farmers in zero waste-based sago processing. The program implementation of the activity showed that the application implementation of zero waste technology in sago processing in Koyani village, Manokwari Regency, immensely helped partners improve their knowledge, skills, and environmental sanitation. Partners Mitra have been skillful in applying semi-mechanical sago starch processing technology using shredded sago rasping machines to increase the sago starch production in both quantity and quality. Of sago starch. Mitra Partners has also made some variations in processed cakes products made of sago starch (sago starch-based cakes). This is one of the efforts to increase the utilization use of sago both as a source of local food for Papua and to support national food security programs based on local potential. Sago waste produced can be used to create made into sago waste briquettes. There is a need for venture capital support assistance and ongoing approaches continuously assistance from local government relevant agencies to develop small-scale creative industries based on local natural resources. --- Program Kemitraan Masyaakat ini bertujuan untuk membangun kemitraan dengan petani sagu dalam pengolahan sagu berbasis zero waste. Hasil pelaksanaan kegiatan menunjukkan bahwa program penerapan teknologi zero waste pada pengolahan sagu di Kampung Koyani Manokwari sangat membantu Mitra dalam meningkatkan pengetahuan, keterampilan, dan sanitasi lingkungan. Mitra telah terampil dalam menerapkan teknologi pengolahan pati sagu secara semi mekanis menggunakan mesin parut sagu sehingga meningkatkan kuantitas dan kualitas pati sagu. Mitra juga telah mampu membuat variasi olahan kue berbasis tepung sagu. Hal ini merupakan salah satu upaya untuk meningkatkan pemanfaatan sagu sebagai sumber pangan local Papua dan mendukung program ketahanan pangan nasional berbasis potensi lokal. Limbah ampas sagu yang dihasilkan dapat dibuat menjadi briket ampas sagu. Perlu adanya bantuan modal usaha dan pendampingan berkelanjutan dari instansi terkait agar mampu menciptakan industri kreatif skala kecil berbasis sumber daya alam local.